Cooperation, sharing and collaboration: the case o f the network of libraries and information centers on art in the estate of Rio de Janeiro - REDARTE/RJ (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
This paper aims to identify and analyze the actions in the Network of Libraries and Information Centers on Art in the State of Rio de Janeiro (Rede de Bibliotecas e Centros de Informação em Arte no Estado do Rio de Janeiro – REDARTE/RJ), in order to promote the production of new knowledge and implementation of new ideas, minimizing the difficulties met by information professionals who work in institutions which integrate the Network, so that to optimize the users services and the enrichment in the thematic field of Information on art. It investigates if the organizational and informational culture of REDARTE/RJ supports cooperation, collaborative work, information and experience sharing and the use of information and communication technology. It analyses the process of cooperation, sharing and collaboration among the participants of REDARTE/RJ, aiming to verify if the Network might be considered a social knowledge network. It seeks to understand the way that REDARTE/RJ has used and taken advantage of the interaction and collaboration as means to the accomplishment of the purposes determined in its bylaws. It comes to the conclusion that REDARTE/RJ has had a relevant role in Information on art, and has been useful to its users and to the professionals and institutions which are part of it, but in order to become a social knowledge network, there are still some aspects to be improved. Keywords: Information on Art. Networks. Informational Culture. Cooperation. Sharing. Collaboration. Information Management. Knowledge Management.Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3126/2466